Integrasi Prinsip-Prinsip Pengendalian Diri dalam Filsafat Stoikisme dan Al-Qur’an sebagai Solusi untuk Kehidupan Modern - Ali Abdurahman Simangunsong; Rijal, Syamsul (Aqlania, 2024)
The life of modern society, which is currently marked by the development of technology and communication, has shown significant progress. However, it turns out that this progress has also given rise to quite complex problems. The pressures of life in this era have diminished individuals' ability to practice self-control, making them vulnerable to various mental and spiritual illnesses. By combining the principles of Stoicism philosophy and the teachings of the Quran, this research explores how self-control can serve as an effective solution to various life challenges nowadays. The method used is qualitative, and data from various literature sources were collected to analyze the principles of self-control from both perspectives. The findings indicate that self-control can be achieved by combining Stoic principles and Quranic teachings. Both provide effective guidance for managing emotions and directing behavior positively in the face of modern life's challenges. The integration of these perspectives offers a holistic and practical approach to enhancing self-control through the development of self-awareness, determination to accept Allah's decrees, thinking before acting, and exercising patience when facing trials in life.